2001
DOI: 10.1001/archpedi.155.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes From Television Sets Toppling Onto Toddlers

Abstract: The injuries reported are not trivial. Not only did they require hospitalization, but they also resulted in an in-hospital death rate comparable to the 2.5% rate observed in children of the same age group injured by unintentional blunt trauma, inclusive of motor vehicle traffic-related injuries. Since virtually all American children are at risk for such injury, we suggest that television set designs be modified to reduce the incidence and severity of the problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
91
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(102 citation statements)
references
References 6 publications
7
91
2
1
Order By: Relevance
“…In various articles, head trauma after TV tip overs has been reported especially in boys (4,6,7). Although the number of boys and girls was equal in this study, the number of male patients in the cases aged between 0 and 3 is clearly higher (Table I).…”
Section: █ Discussioncontrasting
confidence: 51%
“…In various articles, head trauma after TV tip overs has been reported especially in boys (4,6,7). Although the number of boys and girls was equal in this study, the number of male patients in the cases aged between 0 and 3 is clearly higher (Table I).…”
Section: █ Discussioncontrasting
confidence: 51%
“…[1,2] Television (TV) falls are a significant cause of morbidity and mortality in pediatric patients, most frequently among those between 0 and 5 years of age, and tend to result in head, thoracic and extremity injuries. [3,4] There are few studies documenting this relatively unknown problem in the pediatric literature. [5] The rising number and nature of pediatric injuries secondary to falling TV sets correlate with the increasing number of home TVs sold per year.…”
Section: Resultsmentioning
confidence: 99%
“…This popular electronic item is a relatively unknown in-home hazard, and a small number of previous studies have documented TV falls as a significant cause of morbidity and death in younger pediatric patients. [3][4][5] Previous studies suggest that the incidence of these types of injuries may be on the rise. [4,6] DiScala et al [4] reported 183 injured children from the National Pediatric Trauma Registry over a 10-year period, and Scheidler et al [3] reported 43 cases over 10 years from the Pennsylvania Trauma Outcome Study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Similar systematic error is obvious in the selection of patients (Group 1) by Gnanaraj et al 1 when compared to previously published studies characterizing the morbidity and mortality of head injuries associated with falling televisions. [10][11][12] Remarkably, four of the nine children (44.4%) with accidental head injuries in Group 2 by Gnanaraj et al 1 had retinal haemorrhages.…”
mentioning
confidence: 91%